Conversion of a High-Altitude Temperate Forest for Agriculture Reduced Alpha and Beta Diversity of the Soil Fungal Communities as Revealed by a Metabarcoding Analysis - Navarro-Noya, Yendi E.; Montoya-Ciriaco, Nina; Muñoz-Arenas, Ligia C.; Hereira-Pacheco, Stephanie; Estrada-Torres, Arturo; Dendooven, Luc (Frontiers in Microbiology, 2021)
Land-use change is one of the most important drivers of changes in biodiversity. Deforestation for grazing or agriculture has transformed large areas of temperate forest in the central highlands of Mexico, but its impact on soil fungal communities is still largely unknown. In this study, we determined how deforestation of a high-altitude temperate forest for cultivation of maize (Zea mays L.) or husbandry altered the taxonomic, phylogenetic, functional and beta diversity of soil fungal communities using a 18S rRNA metabarcoding analysis. The true taxonomic and phylogenetic diversity at order q=1, i.e. considering frequent OTUs, decreased significantly in the arable, but not in the pasture soil. The beta diversity decreased in the order forest>pasture> arable soil. The ordination analysis showed a clear effect of intensity of land-use as the forest soil clustered closer to pasture than to the arable soil. The most abundant fungal phyla in the studied soils were Ascomycota, Basidiomycota and Mucoromycota. Deforestation more than halved the relative abundance of Basidiomycota; mostly Agaricomycetes, such as Lactarius and Inocybe. The relative abundance of Glomeromycota decreased in the order pasture>forest>arable soil. Symbiotrophs, especially ectomycorrhizal fungi, were negatively affected by deforestation while pathotrophs, especially animal pathogens, were enriched in the pasture and arable soil. Ectomycorrhizal fungi were more abundant in the forest soil as they are usually associated with conifers. Arbuscular mycorrhizal fungi were more abundant in the pasture than in the arable soil as the higher plant diversity provided more suitable hosts. Changes in fungal communities resulting from land-use change can provide important information for soil management and the assessment of the environmental impact of deforestation and conversion of vulnerable ecosystems such as high-altitude temperate forests.